The Effect of Pricing and Promotion on Online Advertising on Social Media on Buying Interest in Wedding packages at Alila Villas Uluwatu - Maharani, Putu Ayu Yoga (PT FORMOSA CENDEKIA GLOBAL, 2024)
The sample of this study consisted of 100 people who were selected as respondents. Data was collected through a questionnaire using a Likert scale. This study uses the SPSS version 25 statistical program to analyze the data. The analysis includes testing data quality (validity and reliability), fulfilling classical assumptions, and modeling the relationship between variables using multiple linear regression analysis. The t and F hypothesis tests were used to test the significance of the model and regression coefficients. The research findings found a positive and significant influence of pricing and online advertising on social media on the interest in buying a wedding package at Alila Villas Uluwatu. The results of this study indicate that the Price Variable (X1) and Online Advertising (X1) simultaneously have a positive and significant effect on buying interest (Y) wedding packages at Alila Villas Uluwatu. The sample of this study consisted of 100 people who were selected as respondents. Data was collected through a questionnaire using a Likert scale. This study uses the SPSS version 25 statistical program to analyze the data. The analysis includes testing data quality (validity and reliability), fulfilling classical assumptions, and modeling the relationship between variables using multiple linear regression analysis. The t and F hypothesis tests were used to test the significance of the model and regression coefficients. The research findings found a positive and significant influence of pricing and online advertising on social media on the interest in buying a wedding package at Alila Villas Uluwatu. The results of this study indicate that the Price Variable (X1) and Online Advertising (X1) simultaneously have a positive and significant effect on buying interest (Y) wedding packages at Alila Villas Uluwatu.